2016
DOI: 10.1074/jbc.m115.679910
|View full text |Cite
|
Sign up to set email alerts
|

Novel KCNJ10 Gene Variations Compromise Function of Inwardly Rectifying Potassium Channel 4.1

Abstract: The KCNJ10 gene encoding Kir4.1 contains numerous SNPs whose molecular effects remain unknown. We investigated the functional consequences of uncharacterized SNPs (Q212R, L166Q, and G83V) on homomeric (Kir4.1) and heteromeric (Kir4.1-Kir5.1) channel function. We compared these with previously characterized EAST/SeSAME mutants (G77R and A167V) in kidney-derived tsA201 cells and in glial cell-derived C6 glioma cells. The membrane potentials of tsA201 cells expressing G77R and G83V were significantly depolarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…7). Interestingly, several single nucleotide polymorphisms (SNPs) that change the biophysical properties of Kir4.1 have been described in the KCNJ10 gene 45 . It is tempting to speculate that other unexplained variants of hypokalemia might be linked to polymorphisms in Kcnj10 / Kcnj16 or other molecular players involved in the direct adaptation of ENaC and ROMK function to altered plasma K + concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…7). Interestingly, several single nucleotide polymorphisms (SNPs) that change the biophysical properties of Kir4.1 have been described in the KCNJ10 gene 45 . It is tempting to speculate that other unexplained variants of hypokalemia might be linked to polymorphisms in Kcnj10 / Kcnj16 or other molecular players involved in the direct adaptation of ENaC and ROMK function to altered plasma K + concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The L166Q variant reduced channel function and the Q212R mutant did not reduce overall conductance, but did demonstrate subtle effects on spermine sensitivity (Méndez‐González et al . ). Tanemoto et al .…”
Section: Kir41 and Kir51 Channels In The Distal Tubulesmentioning
confidence: 97%
“…As described by Méndez González et al . (), there are over 120 coding‐region single nucleotide polymorphisms (SNPs) in the KCNJ10 gene reported in the publicly accessible genome databases. Electrophysiological analysis revealed that the currents produced by mutant channels carrying disease‐associated mutations (R65P, R65P/R199X, G77R, C140R, T164I and A167V/R297C) were strongly reduced, indicating that the loss of channel function underlies the EAST/SeSAME syndrome (Williams et al .…”
Section: Kir41 and Kir51 Channels In The Distal Tubulesmentioning
confidence: 99%
“…We found a rare predicted-deleterious variant in KCNJ10, a gene previously implicated in symptom development and recovery following mTBI. 53 KCNJ10 encodes the potassium channel Kir4.1, an inwardly rectifying potassium channel, which restores negative resting potential mediating the clearing of extracellular glutamate. 54 The case patient (R117) identified with a KCNJ10 variant (p.Arg18Trp) presented with recurrent episodes of pallor and vomiting following minor head injuries.…”
Section: Potassium Channelsmentioning
confidence: 99%